Search for quantum black hole production in lepton + jet final states using proton-proton collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Schöning, André; Schultz-Coulon, Hans-Christian; Spieker, Thomas; et al. (Physical review, 2024)
A search for quantum black holes in electron+jet and muon+jet invariant mass spectra is performed with 140 fb−1 of data collected by the ATLAS detector in proton-proton collisions at √𝑠=13 TeV at the Large Hadron Collider. The observed invariant mass spectrum of lepton+jet pairs is consistent with Standard Model expectations. Upper limits are set at 95% confidence level on the production cross section times branching fractions for quantum black holes decaying into a lepton and a quark in a search region with invariant mass above 2.0 TeV. The resulting quantum black hole lower mass threshold limit is 9.2 TeV in the Arkani-Hamed-Dimopoulos-Dvali model, and 6.8 TeV in the Randall-Sundrum model.